Demütigungserzählungen in autobiographischen Texten. Ein Vergleich zwischen Alfons Petzolds «Das rauhe Leben» (1920) und Christian Barons «Ein Mann seiner Klasse» (2020): Narratives of Humiliation in Autobiographical Texts. A Comparison between Alfons Petzold’s «Das rauhe Leben» (1920) and Christian Baron’s «Ein Mann seiner Klasse» (2020) (Studia austriaca, 2024)
This paper delves into autobiographical texts, uncovering thematic and narrative parallels, with a keen focus on the depiction of humiliations in Das rauhe Leben [The Rough Life] by Alfons Petzold and Ein Mann seiner Klasse [A Man of his Class] by Christian Baron. It posits humiliation as both excluding and order-establishing, yet also catalyzing resistance to societal exclusion. Following a theoretical examination of humiliation, the study scrutinizes how it shapes the autobiographical narratives, analyzing narrative techniques, its impact on plot and character, spatial significance, and associated discourses.